Actividad antimicrobiana in vitro del propóleo en el control de Escherichia coli y Staphylococcus aureus - Pinargote Anchundia, Eddy Gregorio (2024)
Escherichia coli and Staphylococcus aureus are two bacterial pathogens that cause a wide variety of infectious diseases in animals; a range of antibiotics are applied without restrictions for their treatment, which has led to the development of antimicrobial resistance. The purpose of the study was to evaluate the in vitro antimicrobial activity of propolis in the control of E. coli and S. aureus. The colorimetric method was applied with the Folin-Ciocalteu reagent for the determination of polyphenolic compounds present in propolis. The susceptibility of the bacteria studied was measured with a millimeter ruler for the determination of the diameter of the inhibition halos expressed in mm. A total polyphenol content of 398.79 + 8.91 mg EAG.100 g-1 propolis and total flavonoids content of 282.20 + 5.50 mg EQ.100 g-1 propolis were obtained. It was evidenced that there are significant differences (p< 0.05) between treatments, as the concentration of propolis extracts increases the value of the inhibition halo was higher, this behavior was observed for both microorganisms. The results of the present work confirm the high effectiveness of propolis extracts on the bacteria investigated; however, a higher bactericidal activity was observed in the control of S. aureus in comparison with E. coli. The excellent antimicrobial activity of propolis extracts at the different concentrations tested was evidenced in the control of the development of Escherichia coli and Staphylococcus aureus, pathogenic bacteria of great importance in animal health.